Faktor-Faktor yang Memengaruhi Kebangkrutan Bank di Indonesia - Hayyu Yunika; Muthmainnah Ananda Putri; Susy Muchtar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The objective of this study is to analyze the factors that contribute to bank bankruptcy in Indonesia. The research utilizes data sourced from the financial statements of Indonesian banking institutions and applies the discriminant method to 43 banks over the period 2020–2024, as published by the Indonesia Stock Exchange (IDX), the Financial Services Authority (OJK), and Bank Indonesia (BI). The findings of this study are expected to assist in preventing bankruptcy within the Indonesian banking sector by identifying factors that potentially lead to financial distress. Furthermore, this research is anticipated to provide valuable insights for bank managers, investors, and regulators. Financial ratios are employed to determine significant differences between bankrupt and healthy banks. Based on the results of this study and prior research, it can be concluded that the Altman model serves as an effective tool for banks to develop models that can predict their potential future operational risks.